2014
DOI: 10.7585/kjps.2014.18.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyantraniliprole against of Bemisia tabaci and Prevention of Tomato Yellow Leaf Curl Virus (TYLCV)

Abstract: To control Bemisia tabaci on tomato, we applied five different combinations of chemical treatments as below: 1) treatment of combinations of cyantraniliprole on the root area and leaf with the existing registered chemicals three times; 2) treatment of combinations of cyantraniliprole on the root area and dinotefuran + emamectin benzoate on the leaf with the existing registered chemicals three times; 3) treatment of combinations of dinotefuran on the root area and cyantraniliprole on the leaf with the existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Despite the application of pesticides for viral disease control, their use poses environmental and health threats. Yield losses due to these pests are estimated at 50% (Hosmani, 2007;Lee et al, 2018). Chilli leaf curl complex, caused by thrips and mites, leads to significant crop losses.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the application of pesticides for viral disease control, their use poses environmental and health threats. Yield losses due to these pests are estimated at 50% (Hosmani, 2007;Lee et al, 2018). Chilli leaf curl complex, caused by thrips and mites, leads to significant crop losses.…”
Section: Introductionmentioning
confidence: 99%
“…Whiteflies are significant crop pests that cause direct and indirect damage (Lee et al 2014). There are many species of whiteflies, (Hidayat et al 2018) reported a dichotomous identification key of whiteflies, completed based on morphological characteristics of 35 collected species in Bogor, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Whiteflies are tiny sugar-robbers that originated from southern Asia but are now found across all regions of the globe, most notably in tropical regions [3,4], except Antarctica [5]. Their aggressive feeding on plant sap from leaf tissue causes substantial losses to agricultural crops [6]. Each female is capable of producing about 320 eggs within a single life cycle [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, B. tabaci is ranked as a highly disastrous insect pest worldwide [11,23]. Due to accumulated impact of direct damage and secondary damages through transmission of viruses, whiteflies pose socioeconomic challenge [6,10]. Many studies across the globe have attempted to reduce its impact on sustainable agricultural productivity [24][25][26].…”
Section: Introductionmentioning
confidence: 99%